2018
DOI: 10.17860/mersinefd.290270
|View full text |Cite
|
Sign up to set email alerts
|

Gaz Yasalarıyla İlgili Geleneksel ve Bağlam Temelli Problemlerin Çözülebilme Durumuna Yönelik Bir Araştırma

Abstract: Öz: Bu çalışmada, üniversite öğrencilerinin bazı gaz yasaları ile ilgili geleneksel ve bağlam temelli problemleri çözebilme durumlarının incelenerek karşılaştırılması amaçlanmıştır. Bu kapsamda, zayıf deneysel desende bir araştırma gerçekleştirilmiştir. Çalışma grubunu, Türkiye'nin batısında bulunan bir devlet üniversitesinde, Fen Bilgisi Öğretmenliği Programı'nda öğrenim görmekte olan 30 birinci sınıf öğrencisi oluşturmaktadır. Çalışmanın verileri, bazı gaz yasaları (Charles Yasası, Gay-Lussac Yasası ve Boyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Besides their wide range of use, all of the units and symbols might be challenging for the students to learn and apply during science courses. The literature indicates that students experience difficulties with units (Bagno, Berger & Eylon, 2008;Furio, Azcona & Guisasola, 2002;Ogunleye, 2009;Oguzhan Dincer & Osmanoglu, 2018;Tan Sisman & Aksu, 2016;Urek & Dolu, 2018). In their study, Tan Sisman and Aksu (2016) found that sixth-grade students held a wide range of misconceptions and errors related to units used for linear, area and volume measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides their wide range of use, all of the units and symbols might be challenging for the students to learn and apply during science courses. The literature indicates that students experience difficulties with units (Bagno, Berger & Eylon, 2008;Furio, Azcona & Guisasola, 2002;Ogunleye, 2009;Oguzhan Dincer & Osmanoglu, 2018;Tan Sisman & Aksu, 2016;Urek & Dolu, 2018). In their study, Tan Sisman and Aksu (2016) found that sixth-grade students held a wide range of misconceptions and errors related to units used for linear, area and volume measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Ogunleye (2009) found that senior secondary school students and their teachers indicated the confusion arising from units and their conversions as a reason for their inability to solve physics problems. Additionally, in their studies, Oguzhan Dincer and Osmanoglu (2018) and Urek and Dolu (2018) determined that science teacher candidates did not have a satisfying performance related to unit conversion. Moreover, Furio et al (2002) reported that university-level chemistry students did not identify 'mole' as a unit; they did not know its meaning and they avoided using it.…”
Section: Introductionmentioning
confidence: 99%
“…Alanyazında basınç konusunda yapılan çalışmalar incelendiğinde daha çok basınç konusunun öğretimine yönelik yaklaşım, yöntem veya tekniklerin (Akgün, Tokur ve Özkara, 2013;Demirel, 2015;Divarcı, 2016;Gök ve Sılay, 2008;Kirişçioğlu, 2007;Yasak, 2017;Yıldırım, 2010), basınç konusuna ilişkin öğretmen görüşlerinin (Sontay ve Karamustafaoğlu, 2018) ve kavram yanılgılarının (Akdemir, 2005;Kaya, Bozdağ ve Ok, 2018;Önen, 2005;Yaman, 2016) araştırıldığı çalışmalar mevcuttur. Bağlam temelli sorular ile ilgili yapılan çalışmalarda ise genellikle öğrencilerin bağlam temelli sorular ile geleneksel soruları cevaplama durumları karşılaştırılmıştır (Can, 2017;Çelik, Akın ve İlhan, 2018;Sak, 2018;Tekbıyık ve Akdeniz, 2010;Ürek ve Dolu, 2018). Alanyazında öğrencilerin bağlam temelli basınç sorularını çözme süreçlerini içeren çalışmalara ise ulaşılamamıştır.…”
Section: Introductionunclassified
“…Alanyazında yer alan yaşam temelli sorularla ilgili yapılan çalışmalar incelendiğinde daha çok yaşam temelli soruların etkinliğinin incelendiği çalışmalara rastlanmaktadır (Akpınar, 2012;Bellocchi, King ve Ritchie, 2016;Benckert ve Petterson, 2005;Broman, Bernholt ve Parchmann, 2015;Chu, Treagust ve Chandrasegaran, 2009;Enghag, 2004;Georghiades, 2006;Heller ve Hallabaugh, 1992;Kurbanoğlu ve Nefes, 2015;McCullough, 2004;Rennie ve Parker, 1996;Palmer, 1997;Park ve Lee, 2004;Sak ve Gürel, 2018;Seddon, 2008;Soobard ve Rannikmae, 2015;Tekbıyık ve Akdeniz, 2010;Ürek ve Dolu, 2018). Bu çalışmalarda yaşam temelli soru içeren testlerin geliştirildiği, fakat testin geçerliği ve güvenirliği üzerinde durulmadığı görülmektedir.…”
Section: Introductionunclassified